Engineering atomic-level complexity in high-entropy and complex concentrated alloys - Hyun Seok Oh (Nature Portfolio, 2019)
Designing complex concentrated alloys with targeted properties for high performance remains challenging because of their complex local atomic environments. Here, the authors show how to engineer atomic-level pressure to customize complexity-induced properties such as solid-solution strengthening.